Barriers and Enablers to Shared Decision Making in Psychiatric Medication Management: A Qualitative Investigation of Clinician and Service Users' Views - Kaminskiy, Emma; Zisman-Ilani, Yaara; Morant, Nicola; Ramon, Shulamit (Frontiers in Psychiatry, 2021)
Shared decision making (SDM) is a recommended health communication in mental health settings. Yet, implementation of SDM in psychiatric consultations discussing medication management is challenging. Insufficient attention has been given to examine the views of both clinicians and service users together about the views and experiences of SDM in psychiatric medication management settings. The purpose of this paper is to examine the views of service users, community psychiatric nurses, and psychiatrists about enablers and barriers of SDM. A thematic analysis of 30 semi structured interviews was conducted. Service users were involved as co-interviewers and in the analysis of interview transcripts. The results offer a detailed contextualized accounts of how medication decisions are made and highlight that SDM is seen as a way of enhancing service users’ engagement in and control over treatment decisions. Service users and psychiatric nurses conceptualize SDM as a long-term endeavor embedded within therapeutic partnerships. For service users these partnerships mitigate acknowledged problems of feeling unable to be fully involved during times of crisis. This study identified a range of barriers and facilitators to SDM concerning psychiatric medications from the lived experience of service users and the professional experience of clinicians. Furthermore, it indicates new potential intervention points to support SDM in psychiatric medication decisions.